Enteric dysbiosis in liver and kidney transplant recipients: a systematic review. (5th August 2020) - Sivaraj, Saranya; Chan, Anita; Pasini, Elisa; Chen, Emily; Lawendy, Bishoy; Verna, Elizabeth; Watt, Kymberly; Bhat, Mamatha
Summary: Several factors mediate intestinal microbiome (IM) alterations in transplant recipients, including immunosuppressive (IS) and antimicrobial drugs. Studies on the structure and function of the IM in the post‐transplant scenario and its role in the development of metabolic abnormalities, infection, and cancer are limited. We conducted a systematic review to study the taxonomic changes in liver (LT) and kidney (KT) transplantation, and their potential contribution to post‐transplant complications. The review also includes pre‐transplant taxa, which may play a critical role in microbial alterations post‐transplant. Two reviewers independently screened articles, and assessed risk of bias. The review identified 13 clinical studies, which focused on adult kidney and liver transplant recipients. Patient characteristics and methodologies varied widely between studies. Ten studies reported increased an abundance of opportunistic pathogens ( Enterobacteriaceae, Enterococcaceae, Fusobacteriaceae, and Streptococcaceae ) followed by butyrate‐producing bacteria ( Lachnospiraceae and Ruminococcaceae ) in nine studies in post‐transplant conditions. The current evidence is mostly based on observational data and studies with no proof of causality. Therefore, further studies exploring the bacterial gene functions rather than taxonomic changes alone are in demand to better understand the potential contribution of the IM in post‐transplant complications.